Health Improvements in BRIC Cities: Moscow, São Paulo, and Shanghai, 2000–10. Issue 2 (June 2016) - Gusmano, Michael K.; Rodwin, Victor G.; Weisz, Daniel; Ayoub, Rafael
Abstract : We compare health improvements among three megacities in BRIC nations as measured by declines in amenable mortality (AM). Although there have been studies of AM in Brazil and the Russian Federation using different definitions and age cohorts, this indicator has never been used to compare these cities. During the period 2000–10, age‐adjusted rates of all leading causes of AM fell in all three cities. In São Paulo, it dropped from 1.57 to 1.19 per 1, 000 population. In Moscow, it fell from 2.10 to 1.40, and in Shanghai, from 0.72 to 0.54. The rate of decrease was highest in Moscow (33 percent), followed by Shanghai (30 percent), and São Paulo (24 percent). All three cities experienced large reductions in chronic cardiovascular diseases in the form of IHD and stroke, but they remain the leading causes of premature death. Our finding of the decline of AM deaths in São Paulo, Moscow, and Shanghai suggests that all three health systems made significant improvements over the 2000–10 period. It will be important to monitor this indicator as economic growth in these countries and cities has slowed considerably since 2010.